Amphetamine Poisoning in a Dog: Case Report, Literature Review and Veterinary Medical Perspectives - Diniz, Pedro Paulo V.P. [UNESP]; Sousa, Marlos G. [UNESP]; Gerardi, Daniel G. [UNESP]; Tinucci-Costa, Mirela [UNESP] (My University, 2003)
Amphetamine abuse in human beings has increased, resulting in many reports of toxicity and death. In the US over 4 million people have abused amphetamines at least once, thus small animals are exposed to increased accidental poisoning risk. This report describes an acute amphetamine poisoning in a dog due to ingestion of 15 mg/kg fenproporex, leading to typical signs of catecholamines release and effects in different organ systems. Similar clinical and laboratory findings observed in human beings are reviewed and physiopathogenic mechanisms discussed, as well as the therapeutic approaches available in veterinary medicine.
Keywords: amphetamine; catecholamine; diazepam; fenproporex; death; disseminated intravascular clotting; dog; drug abuse; drug intoxication; hyperthermia; liver toxicity; male; nephrotoxicity; nonhuman; pathophysiology; restlessness; review; rhabdomyolysis; seizure; tachypnea; tremor; veterinary medicine; vomiting; Amphetamines; Animals; Diagnosis, Differential; Dog Diseases; Dogs; Emergency Treatment; Fatal Outcome; Male; Poisoning; Animalia; Canis familiaris